The impact of physical exercise on academic satisfaction among middle-school students: the mediating roles of social support and depression - Huo, Xing; Guan, Jinhuan; Tian, Haibo (Frontiers in Psychology, 2026)
IntroductionThe association between physical exercise and academic satisfaction is a crucial topic in recent research. However, existing literature has paid insufficient attention to exploring the influence of physical exercise on academic satisfaction, particularly regarding the mediating role of social support and depression.MethodsA sample of 564 Chinese middle-school students was randomly recruited from five high schools in Shaoxing City. We proposed a hypothesized model to examine the relationship between physical exercise, academic satisfaction, social support, and depression.ResultsResults from PROCESS v4.1 for SPSS revealed that physical exercise had a significant and positive impact on both academic satisfaction and social support; Social support showed a positive association with academic satisfaction; Physical exercise, social support, and academic satisfaction were significantly negatively correlated with depression; Furthermore, social support and depression partially mediated the relationship between physical exercise and academic satisfaction.DiscussionThese findings provide empirical evidence into elucidating how physical exercise promotes high school students’ academic satisfaction. The limitations and future directions of these findings are discussed.